Personal Network Size and Social Accompaniment: Protective or Risk Factor for Momentary Loneliness, and for Whom?. (March 2023) - Goldman, Alyssa W.; Compernolle, Ellen L.
Personal networks yield important health benefits for individuals, in part by providing more opportunities to be in the company of others throughout daily life. Social accompaniment is generally believed to protect against momentary feelings of loneliness, although this hypothesis remains understudied. We examine how personal network size shapes older adults' experiences of momentary loneliness and whether this association varies by momentary social accompaniment. We use three waves of ecological momentary assessments (EMA; N = 12, 359) and personal network data from 343 older adults in the Chicago Health and Activity Space in Real-Time study. Older adults with large personal networks experienced more intense momentary loneliness compared with those with smaller social networks when they were momentarily alone. This association was more pronounced among men. We discuss how research approaches that bridge global and momentary measures of social connectedness can reveal important nuances of our understanding of how interpersonal factors influence later-life well-being over time.